On the relationship between language learning strategy use and motivation - Masoud Rahimi Domakani,; Ali Roohani,; Roghayeh Akbari, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
A shift of attention has taken place in second/foreign language (L2) learning research from the products of learning to the processes through which learning takes place. Thus, L2 researchers have turned their attention to the role that language learning strategies play in L2 learning/teaching. Given that L2 learning and teaching is difficult and needs motivation, this study investigates second language (L2) learning strategy use as well as instrumental and integrative types of motivation. Besides, it explores the relationship between L2 learning strategy use and motivation in a sample of 152 EFL learners at two Iranian universities. To collect data, Strategy Inventory for Language Learning (SILL) and a motivational questionnaire were used. The collected data were analyzed descriptively and inferentially using correlation. Results showed that, first, Iranian EFL participants, in general, had a moderately high level of motivation toward learning English. Second, they were more integratively motivated. Third, compensation strategies were the leading strategy type and social strategies were the least common reported type of strategy. Fourth, motivation correlated positively with all types of language learning strategies. Finally, the implications of the findings for L2 research and pedagogy are presented.